KEMAHIRAN MENULIS CERITA PENDEK DENGAN MODE SUGESTI IMAJINASI MEDIA LAGU DAN VIDEO KLIP PESERTA DIDIK BERINTELEGENSI MUSIK TINGGI DAN BERINTELEGENSI MUSIK RENDAH SMA 1 MEJOBO (Universitas Negeri Semarang, 2013)
This study is aimed to determine (1) the effectiveness of the use of suggestion models media imagination songs and video clips to enhance the skills of writing short stories high school students of class X music high and low capability, (2) the effectiveness of the intelligence factor of music on short story writing skills high school students of class X and (3) the relationship between the model suggestion imagination song and video media clips with music capability X. grade school students.The method is experimental design. Technical research data collection using instruments short story writing skills, multiple intelligence test, and sheet observation. Conclusion The results of this study were (1) the use of media imagination song suggestions models effective for students music with high capability ,imagination and suggestion models use media effectively for video clips music learners with low capability, (2) short story writing skills of students with high music capability is different from short story writing skills of students with music low capability, (3) a model of suggestion and imagination of the media song video clips influence short story writing skills of students high school class X